The Urgency of WTO Reform: Impact of Nickel Dispute (DS529) on Indonesia Nickel Trade - Meichella, Aziizah; Diningrat, Aqil; Gurnita, Ni Luh; Akim, Akim (Journal of World Trade Studies, 2024)
This paper examines the need for reform of the WTO dispute settlement body and a comprehensive review of the organization’s structure. It examines the main reasons behind the reform urgencies by examining dysfunctions occurring in the dispute settlement procedure. This paper further argues that the structural and functional problems of WTO could disrupt Indonesia's trade relation with the European Union and the export of nickel raw materials around the world, and therefore worth solving. Due to its complex nature, the paper admits the complications rising within the domestic trade and the bureaucracy. This paper will specifically break down the problem, address the actors, and describe the reason behind the problem's persistence. Furthermore, instead of simply looking back at the phenomenon, this paper investigates the solutions made by the government through mass media. This paper finds that the main problem lies between the internal affairs of the WTO, thus the recommendations: (i) review of the entire WTO structure's function; (ii) eliminate special treatment provisions that disadvantage developing countries; and (iii) restructure the dispute settlement body. In addition, this paper presents Indonesia’s efforts in repairing the impacted nickel trade by road-mapping investments with foreign private sectors, as well as strategizing MPIA to settle this dispute during the downstreaming implementation and reformation process.